Laboratory Evolution Assays and Whole-Genome Sequencing for the Development and Safety Evaluation of Lactobacillus plantarum With Stable Resistance to Gentamicin - Dong, Yushan; Zhang, Fuxin; Wang, Bini; Gao, Jiayuan; Zhang, Jiangtao; Shao, Yuyu (Frontiers in Microbiology, 2019)
The goal of this work was to use laboratory evolution assays and whole-genome sequencing to develop and test the safety of a probiotic, Lactobacillus plantarum, with high-level of resistance to gentamicin. The evolution of L. plantarum was evaluated under the selective pressure from gentamicin and subsequently when the selective pressure was removed. After 30 d of selective pressure from gentamicin, the minimum inhibitory concentration (MIC) of L. plantarum to gentamicin increased from 4 μg/mL to 512 μg/mL and remained stable at this level. After removing the selective pressure, the resistance of L. plantarum to gentamicin decreased to 64 μg/mL after 20 d, and remained stable thereafter. Although the MIC declined it was still higher than the cut-off value recommended by EFSA, indicating that the acquisition of gentamicin-resistance was an irreversible process. Using whole-genome sequencing, gene mutations were identified in the strains that had undergone selection pressure from gentamicin as well as in the strains where the selection pressure was subsequently removed. Specifically, four non-synonymous mutations were detected including one single nucleotide polymorphism (SNP), one insertion, and two structural variants (SVs), of which the mutations in genes encoding the drug resistance MFS transporter and transcriptional regulator of AraC family were only detected in the strains under selective pressure from gentamicin. The results indicate that these mutations play an important role in increasing the resistant levels of L. plantarum to gentamicin. The mobility analysis of mutant genes confirmed that they were not located on mobile elements of the genome of highly resistant L. plantarum, indicating that horizontal gene transfer was not possible.